2013
DOI: 10.1186/2045-9912-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Xenon preconditioning: molecular mechanisms and biological effects

Abstract: Xenon is one of noble gases and has been recognized as an anesthetic for more than 50 years. Xenon possesses many of the characteristics of an ideal anesthetic, but it is not widely applied in clinical practice mainly because of its high cost. In recent years, numerous studies have demonstrated that xenon as an anesthetic can exert neuroprotective and cardioprotective effects in different models. Moreover, xenon has been applied in the preconditioning, and the neuroprotective and cardioprotective effects of xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…In recent years, other medical gases such as xenon and methane are speculated to be able to act on some proteins. For example, xenon can potently inhibit the N-methyl-D-aspartate (NMDA) receptors non-competitively 33 and methane might confer an effect on membrane channels 34 . Thus, more studies are needed to elucidate the specific influence of hydrogen gas on these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, other medical gases such as xenon and methane are speculated to be able to act on some proteins. For example, xenon can potently inhibit the N-methyl-D-aspartate (NMDA) receptors non-competitively 33 and methane might confer an effect on membrane channels 34 . Thus, more studies are needed to elucidate the specific influence of hydrogen gas on these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The inhaled anesthetic gases can be used as either a pre-conditioning approach or a post-conditioning one. Preconditioning has demonstrated protective effects against TBI (Harris et al, 2013;Deng et al, 2014;Khan et al, 2015;Shu et al, 2016), ischemic stroke (Dingley et al, 2006;Wang et al, 2011Wang et al, , 2016Yu et al, 2011;Liu et al, 2013;Shi et al, 2013), and hemorrhagic stroke (Gigante et al, 2011;Sheng et al, 2012). Post-conditioning is a relative new concept and it has been reported in ischemic stroke (Li et al, 2014;Yin et al, 2014;Lee et al, 2015;Liu et al, 2016).…”
Section: Protective Effect Of Inhaled Anesthetic Gasesmentioning
confidence: 99%
“…Xe is a noble gas used in general anesthesia. [5] Studies have shown that xenon has protective effects on ischemia-reperfusion injury of brain . [6,7] Moreover, xenon exhibited neuroprotective activity for the treatment of ischemic brain injury in combination with mild hypothermia in animal models.…”
mentioning
confidence: 99%